2006
DOI: 10.4070/kcj.2006.36.12.802
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Coronary Atherosclerosis; Influence of Metabolic Syndrome Risk Factor Clustering and hs-CRP

Abstract: Background and Objectives:Metabolic syndrome and high sensitivity C-reactive protein (hs-CRP) are known to be strong predictors of coronary atherosclerosis. Even though there have been many observations and much research concerning the association of coronary atherosclerosis with CRP and metabolic syndrome, certain problems still need to be resolved in order to produce clear mechanistic illustrations. Therefore, the correlations of metabolic syndrome, hs-CRP and the severity of coronary atherosclerosis were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…However considering MetS with regards to coronary atherosclerosis; a low-grade inflammatory process with visceral obesity is strongly associated with coronary atherosclerosis. 16)17) In this study, there was a significant correlation between CAC and MetS. This result is consistent with the result from the previous study which demonstrated the relationship between CAC and Mets 18-20).…”
Section: Discussionsupporting
confidence: 92%
“…However considering MetS with regards to coronary atherosclerosis; a low-grade inflammatory process with visceral obesity is strongly associated with coronary atherosclerosis. 16)17) In this study, there was a significant correlation between CAC and MetS. This result is consistent with the result from the previous study which demonstrated the relationship between CAC and Mets 18-20).…”
Section: Discussionsupporting
confidence: 92%
“…Rate of obesity is increasing globally where studies have shown association of body weight as assessed by body mass index (BMI) with clinical outcomes after percutaneous coronary intervention (PCI) in acute myocardial infarction (AMI) patients 3). Previous reports have also indicated that hs-CRP level is correlated with BMI and fat distribution 4)5). The mechanism for elevation of plasma hs-CRP in obese subjects could be through a high production of cytokines, e.g., interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), by excess adipose tissue which could induce high hs-CRP production in liver 4)…”
Section: Introductionmentioning
confidence: 99%
“…The association of increased serum levels of acute-phase proteins with the progression of atherosclerosis and with the occurrence of atherosclerosis-related adverse events, such as coronary heart disease and myocardial infarction (MI), has been well documented in several epidemiological studies. 1 - 6) …”
Section: Introductionmentioning
confidence: 99%